Geochemical characteristics of the upper triassic Bagong formation mudstones in the eastern North Qiangtang depression and their constraints on the provenance, palaeoclimate and palaeoenvironment - Peng, Qinghua; Du, Baiwei; Peng, Jie; Liu, Zhenfeng; Danzeng, Pingcuo (Frontiers in Earth Science, 2025)
The black mudstones of the Upper Triassic Bagong Formation, Qiangtang Basin, are important hydrocarbon source rocks, but significant differences are found in their quality across the region; thus, the genetic mechanism of these mudstones needs to be revealed to determine the spatial distribution of the high-quality hydrocarbon source rocks in the Bagong Formation of the North Qiangtang Depression. To elucidate the genetic mechanism of the Bagong Formation mudstones, 31 samples of the Bagong Formation mudstones from the Tielong Section in the eastern North Qiangtang Depression were collected and analysed to determine their total organic carbon (TOC) and major and trace element contents. The results revealed that the Bagong Formation mudstones in the study area had a low to moderate TOC contents; these results indicated that they were poor to moderate hydrocarbon source rocks. The elemental geochemical characteristics indicate that the provenance of the Bagong Formation mudstones in the study area was mainly felsic rocks that formed in collisional tectonic settings; these results are consistent with the tectonic regime of early Late Triassic intracontinental compression in the North Qiangtang Depression. During the deposition of the Bagong Formation mudstones, the climate was warm and humid, and the environment was a shallow oxidizing saltwater column, with a large input of rapidly deposited fine-grained argillaceous detritus. The warm and humid climate conditions and rapid sedimentation rate during the deposition of the Bagong Formation mudstones in the study area promoted the preservation of partly organic matter; however, the overall abundance of organic matter remained low because of the influence of the oxidizing water column.